Selection of the cutoff value of the tuberculin skin test for diagnosing students who need preventive treatment: A school-based cross-sectional study - Lu, Peng; Ding, Xiaoyan; Sun, Jiansheng; Wang, Rong; Liu, Jiasong; Liu, Qiao; Zhu, Limei; Lu, Wei (Frontiers in Cellular and Infection Microbiology, 2022)
Objective Tuberculosis outbreaks in schools are common in China. This study aimed to introduce and evaluate a new screening process to help control outbreaks. Methods Screening information of students in three schools with tuberculosis outbreaks was collected. QuantiFERON-TB gold in-tube (QFT) results were used as the reference standard to determine the cutoff value of the tuberculin skin test (TST) for diagnosing students who need to have preventive medication. Results A total of 1,232 students and teachers from three different schools that all had more than three student patients with tuberculosis were included in this study. In total, 308 (25.0%) students had an induration diameter ≥10 mm; among students in a class different from the index case, the infection rate was 24.4% (264/1,084), which was lower than the rate among students in the same class (29.7%) (P = 0.157). Students in the same class as the index tuberculosis case had a much higher QFT positivity compared to those in a different class (58.1% vs. 7.7%, P < 0.0001). Diagnostic agreement between TST ≥10 mm and QFT was 36.6%. The diagnostic value reached the highest when the induration diameter of TST was ≥9 mm, with a sensitivity and specificity of 94.1% (95% CI: 89.4%–97.1%) and 27.6% (95% CI: 24.9%–30.4%), respectively. The area under the curve (AUC) was 0.664 (95% CI: 0.637–0.690, P < 0.0001). Conclusion In tuberculosis outbreaks in schools, if there are three or more cases of students with tuberculosis in a class or if the moderate or strong TST positivity rate is much higher than the normal range in the region, attention should be paid to those with moderately positive TST results. Interferon-gamma release assays (IGRAs) are recommended to be conducted following TST on the day of reading the results, especially among students sharing the same class with the index case. In resource-poor areas lacking IGRAs, the induration diameter of TST can be appropriately reduced from 15 to 9 mm to enhance the sensitivity of TST.